Genetics of the monogenic forms of dyslipidaemia - Bourbon, Mafalda (2019)
Familial hypercholesterolemia (FH) is an autosomal dominant disorder associated with high levels of LDL-c and premature CHD (pCHD). Identification of FH in pediatric age is essential for a timely diagnosis and management. This study aims to highlight the importance of FH diagnosis in children.